Dominance of Unsafe Acts as the Primary Cause of Occupational Accidents - Kurniasari, Widhati; Lestari, Fatma (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Occupational accidents remain a significant issue in occupational health and safety (OHS), particularly in manufacturing industries characterized by high production demands. This study aimed to analyze the causal factors of workplace accidents, with a specific focus on unsafe acts and unsafe conditions in a footwear manufacturing industry. A quantitative descriptive analytic design with a cross-sectional approach was employed, using secondary data on occupational accidents at PT X from January to June 2025. Total sampling was applied, and data were analyzed using frequency and proportional distribution to identify the dominant causal factors. The results indicate that unsafe acts were the predominant cause of occupational accidents. Most incidents were classified as first-aid cases with minor severity and occurred repeatedly, suggesting inadequate supervision. Common unsafe acts were closely related to non-compliance with safety procedures, such as failing to maintain a safe distance, adopting unsafe working positions, and not turning off machinery. Unsafe conditions were identified in fewer cases; however, they functioned as contributing factors that potentially exacerbated accident severity. In conclusion, this study explicitly demonstrates that unsafe acts are the dominant cause of occupational accidents in the observed manufacturing setting. Therefore, accident prevention strategies must primarily prioritize behavior-based interventions, supported by systematic improvements in supervision, work systems, and the work environment to ensure more effective and sustainable prevention outcomes.Keywords: occupational accidents; manufacturing industry; unsafe acts; unsafe conditions